2021
DOI: 10.24203/ajafs.v9i2.6615
|View full text |Cite
|
Sign up to set email alerts
|

Quality Deterioration of Postharvest Fruits and Vegetables in Developing Country Pakistan: A Mini Overview

Abstract: Post-harvest losses relate to the degradation in the quantity and quality of the crop’s products from harvesting to consumer usage. In many developing countries, like Pakistan, the post-harvest loss is a problem of food security and is of concern to everyone. Inappropriate handling of agricultural products after harvest may cause quality and quantity losses. It also accounts for the increasing prices of agricultural products in Pakistan. The total production of vegetables and fruits in Pakistan is nearly 13.76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These genes were expressed in both plant tissues, although in B. juncea they were slightly higher than in B. napus . These different expressions of shattering genes shows that they are important for cellular valve and margin evolution [ 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genes were expressed in both plant tissues, although in B. juncea they were slightly higher than in B. napus . These different expressions of shattering genes shows that they are important for cellular valve and margin evolution [ 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol-containing films inhibited the growth of Rhizopus sp and Penicillium sp. Even when optimal conditions are provided during distribution, agricultural products have a short shelf life from the time of harvest due to quality degradation between harvest and consumption (Sangeetha et al;Ahmad et al, 2021). If the product is not handled properly, this loss in quality could be significant.…”
Section: Pla-carvacrol Essential Oilmentioning
confidence: 99%
“…Panama disease caused by a fungus (Fusarium oxysporum) also named as Fusarium wilt disease is also affecting the yield of many banana varieties and is a global threat for the banana production (Ganga and Chezhiyan, 2002). It is reported that the total post-harvest of bananas amounted to Pakistan has been 154,825 tons from 34, 830 hectares per year (Ahmada et al, 2021).…”
Section: Banana (Musa Spp)mentioning
confidence: 99%